Typical development of the human fetal subplate: Regional heterogeneity, growth, and asymmetry assessed by in vivo T2-weighted MRI - Andrea Gondová; Jennings Zhang; Sungmin You; Seungyoon Jeong; Milton Osiel Candela-Leal; Caitlin Kantrowitz Rollins; Patricia Ellen Grant; Hyuk Jin Yun; Kiho Im (Proceedings of the National Academy of Sciences, 2026)
The subplate (SP) is a transient fetal brain compartment supporting neuronal migration, axonal ingrowth, and early cortical activity, yet the dynamics of its regional development remain poorly understood in vivo. Using T2-weighted fetal MRI of 68 typically developing fetuses (22 to 32 wk gestational age, GA), we developed a semiautomated pipeline to quantify regional SP morphology (thickness, surface area, and volume). SP characteristics scaled strongly with GA and residual brain volume and showed marked regional differences. After correcting for geometric confounds, regional variation of SP thickness persisted, with highest values in parietal and perisylvian regions, suggesting that SP thickness may serve as a sensitive marker of intrinsic developmental differences. Between the late 2nd and early 3rd trimesters, mean SP thickness increased by 39.2% with large variation across regions (±11.0 SD), whereas surface area growth was more uniform (64.3% ±0.7 SD). Continuous growth trajectories clustered into distinct spatiotemporal profiles: early-developing regions (e.g., pericentral and medial occipital cortices) contrasted with later-developing regions (prefrontal, temporal, and parietal cortices). These patterns partially recapitulate primary-to-association, medial-to-lateral, and posterior-to-anterior maturational hierarchies, pointing to organized developmental programs. SP development also showed region-specific hemispheric asymmetries, including leftward thickness and volume asymmetry in the superior temporal and precentral gyri. Some asymmetries amplified, others attenuated or reversed with age, suggesting both transient states and potential precursors of postnatal lateralization. Together, these findings provide a framework for regional SP quantification and position SP morphology, particularly thickness, as a promising early biomarker that might link fetal SP changes to subsequent cortical development and neurodevelopmental outcomes.